Chinese brocade - Yang, Charles (2011)
Chinese brocade located above the balcony door in the meeting hall of the Lee Association (614 Fisgard Street, Victoria, B.C.). Primarily red and gold, with gold fishnet fringe and multi-coloured tassels, the embroidery depicts human and animal figures against a background of flowers and leaves. Photo taken for Lee Association picture collection. Derivative displaying only the brocade from the original picture taken on June 11, 2011.